An ecological dynamics perspective on designing urban nature environments for wellbeing and health-enhancing physical activity - Brito, Henrique; Brymer, Eric; Araújo, Duarte (Frontiers in Public Health, 2022)
The latest World Health Organization report on green and blue space and mental health (2021) calls for greater, and better, urban nature environments, i.e. “wilder” urban parks, tree-laden sidewalks, and overall presence of nature in the urban environment. Evidence shows that living close to and interacting with nature promotes benefits to numerous health and well-being indicators. The present article narratively reviews what are the aspects of urban nature environments that enhance health and well-being markers, which aspects are preferred among users and visitors of urban nature environments, and how can the benefits for health and well-being be understood from a theoretical perspective. Finally, guided by the ecological dynamics framework, suggestions are put forward on how designers and planners of urban nature environments can consider affordances to promote physical activity behavior, health and well-being; and how exercise and health researchers and professionals may channel the interaction of individuals with the nature environment in their interventions and programs.